Children's book publication in Lithuania in 1940-1955 - Vita Mozūraitė (Knygotyra)
The State Publishing House of the Lithuanian SSR and some private publishing houses published children's books during the period from June 1940 until June 1941. They published 49 children’s books in 277,500 copies. During the German occupation, children's books were published in Moscow, where the State Publishing House operated, and some were published in Lithuania. After the end of the war in 1945, new publishing houses were established in Lithuania, and all of them published books for children.